Cutaneous manifestations of patients with Human Immunodeficiency Virus (HIV) Infection: A retrospective review of a tertiary referral centre with clinicopathological correlation. (17th March 2021) - Han, Winn Hui; Yong, Jo Yen; Yong, Shin Shen; Faheem, Nik Aimee Azizah; Toh, Yen Fa; Chew, Man Fong; Kwan, Zhenli; Azwa, Iskandar
Abstract: Introduction: The majority of patients with Human Immunodeficiency Virus (HIV) will have cutaneous manifestation during their disease course. We report the spectrum of cutaneous manifestations and clinicopathological concordance in the diagnosis of skin diseases in patients with HIV. Methods: A retrospective review of all cutaneous manifestations of HIV‐infected patients with skin biopsy‐proven histopathological confirmation, treated in the University of Malaya Medical Centre, from 2016 till 2018, was performed. Clinical characteristics and histopathological correlation of these patients were reviewed. Results: A total of 38 cases were included where the median age was 40.5 (interquartile range (IQR) 13.3). The median duration of HIV diagnosis to the development of skin disease was 3 years (IQR 7.8). Majority of our patients were male (89.5%, n  = 34), and the commonest mode of transmission is men who have sex with men (36.8%, n  = 14). Most patients (92.1%, n  = 35) had Acquired Immunodeficiency Syndrome when they presented with skin diseases, predominantly non‐infectious types (51.4%, n  = 19). Commonest skin diseases include eczema ( n  = 7) and pruritic papular eruption of HIV ( n  = 6). Papules and plaques were the commonest morphology for both infectious and non‐infectious skin diseases. Duration of HIV diagnosis ( P  = 0.018) and non‐compliance to Highly Active Antiretroviral Therapy (HAART) ( P  = 0.014) were significantly associated with the development of non‐infectious skin diseases. Overall, clinicopathological concordance was 84.2% in our centre. Conclusion: A wide spectrum of cutaneous diseases can occur in HIV patients depending on the degree of immunosuppression. skin biopsy along with appropriate stains, and microbiological cultures are important in helping clinicians clinch the right diagnosis.